Annual Financial Statements - Report Of The Independent Auditors (The Southern African Institute of Mining and Metallurgy, 1999)
To the members of The South African Institute of Mining and Metallurgy We have audited the annual financial statements set out on pages 269 to 276. These financial statements are the responsibility of the Institute?s Council. Our responsibility is to report on these financial statements. We have conducted our audit in accordance with generally accepted auditing standards. These standards require that we plan and perform the audit to obtain reasonable assurance that, in all material respects, fair presentation is achieved in the financial statements. The audit included an evaluation of the appropriateness of the accounting policies, an examination, on a test basis, of evidence that supports the amounts and disclosures included in the financial statements, an assessment of the reasonableness of significant estimates, and a consideration of the appropriateness of the overall financial statement presentation. We consider that our auditing procedures were appropriate in the circumstances to enable us to express our opinion presented here. In our opinion these financial statements fairly present the financial position of the Institute at 30th June, 1999, and the results of its operations for the year then ended in conformity with generally accepted accounting practice.